Defining availability of 100 essential diagnostic items for children with cancer and gaps in implementing WHO recommendations: Global CEDx Working Group survey. (July 2022) - Lam, Catherine G; Alcasabas, Ana Patricia; Antillon, Federico; Calderon, Patricia; Dolendo, Mae; Fu, Ligia; Gamboa, Yessika; Gassant, Pascale; Gomez-Garcia, Wendy; Gunasekera, Sanjeeva; Khaing, Aye Aye; Kizyma, Roman; et al.
Abstract: Background: WHO has established recommendations to guide governments' prioritisation of essential diagnostic tests, technologies, and priority medical devices for patients with cancer. Despite many countries committing to expanding resources for children with cancer since the WHO Global Initiative for Childhood Cancer was launched in 2018, data on the availability of essential diagnostics and on local awareness and adoption of WHO recommendations in low-income and middle-income countries are scarce. Methods: A purposive group of providers and policy makers was invited to review national interventions for access to diagnostics as part of their national cancer control plan or involvement in the WHO Global Initiative for Childhood Cancer. More than 800 diagnostic items (ie, diagnostic tests and diagnostic devices or equipment) from WHO recommendations for priority medical devices for cancer and essential in-vitro diagnostics list were iteratively summarised into 100 items relevant for children with cancer. A survey (in English, Spanish, French, and Russian) was developed to assess diagnostics availability and COVID-19 impact on access; out-of-pocket needs, or financial burden on families to pay for diagnostics; perception of the WHO recommendations with respect to completeness and relevance, use and usefulness for children with cancer; and factors affecting recommendation adoption and implementation. Findings: 380 participants from 16 low-income and middle-income countries in six WHO regions (Costa Rica, Dominican Republic, El Salvador, Ghana, Guatemala, Haiti, Honduras, Morocco, Myanmar, Nicaragua, Panama, Peru, Philippines, Sri Lanka, Ukraine, and Zambia), were invited. The median response rate across the 16 countries was 80%. 231 (80%) of 289 eligible respondents were multidisciplinary clinicians (including 101 paediatric haematologist–oncologists), and 58 (20%) self-identified primarily as administrators, non-governmental organisation representatives, and policy makers. Although some diagnostic items were not available in all settings, disparities were evident. Diagnostic items were significantly more available in the private than in the public setting across all three categories of laboratory and pathology (+25%), surgery and anaesthesia (+19%), and imaging (+43%; p<0·0015 for all categories). Most respondents indicated that at least one in four patients were affected by varying availability of diagnostic items, and that families paid out-of-pocket for essential diagnostic items. Top-ranked priorities by respondents included addressing access to advanced and basic diagnostics, delays in tests, and families' need to pay out-of-pocket. 119 (85%) of 140 eligible respondents considered that the 100 distilled core items reflected a complete list for laboratory and pathology, surgery and anaesthesia, and imaging. Although 69 (87%) of 79 respondents and 155 (90%) of 172 respondents found WHO recommendations useful and relevant, 228 (83%) of 276 had little previous familiarity with the recommendations, and only 82 (29%) of 278 had previously used them, mainly as personal references. Top factors affecting adoption and implementation of WHO recommendations included awareness and ease of extracting and applying recommendations to childhood cancer and to local contexts. Interpretation: This study established the availability of a core set of 100 essential diagnostic items recommended by WHO in low-income and middle-income countries in different phases of expanding access to care for children with cancer. A scarcity of essential laboratory and pathology, surgery and anaesthesia, and imaging diagnostics in all settings were identified, as well as a disproportionate lack of access for patients in the public setting, further disrupted by the COVID-19 pandemic. This study explored local awareness and factors affecting adoption and implementation of WHO recommendations and priorities for policy action. Our findings point to the utility of an essential diagnostics list for children analogous to WHO's essential medicines list. Funding: American Lebanese Syrian Associated Charities and St Jude Children's Research Hospital.